2021
DOI: 10.1016/j.kint.2021.02.035
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of transforming growth factor β1 signaling in resident interstitial cells attenuates profibrotic gene expression and preserves erythropoietin production during experimental kidney fibrosis in mice

Abstract: Inhibition of transforming growth factor β1 signaling in resident interstitial cells attenuates profibrotic gene expression and preserves erythropoietin production during experimental kidney fibrosis in mice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 69 publications
(140 reference statements)
1
13
0
Order By: Relevance
“…In the murine model of early renal fibrosis at day 4 after UUO surgery, we demonstrated that SB431542 could reverse Epo expression in the UUO kidney myofibroblasts through inhibiting TGF-β1-activated ALK5. Our finding could be supported by the recent report that selective disruption of TGF-βR2 in renal PDGFRβ + cells preserves EPO production but no discernible effect on myofibroblast markers in the murine model of renal fibrosis [ 46 ].…”
Section: Discussionsupporting
confidence: 86%
“…In the murine model of early renal fibrosis at day 4 after UUO surgery, we demonstrated that SB431542 could reverse Epo expression in the UUO kidney myofibroblasts through inhibiting TGF-β1-activated ALK5. Our finding could be supported by the recent report that selective disruption of TGF-βR2 in renal PDGFRβ + cells preserves EPO production but no discernible effect on myofibroblast markers in the murine model of renal fibrosis [ 46 ].…”
Section: Discussionsupporting
confidence: 86%
“…Notably, suppression of NFκB signaling with glucocorticoids and genetic disruption of TGFB1 receptor 2 function can protect from loss of EPO production in injured kidneys. 4,32,34 Furthermore, epigenetic reprogramming is likely to play an important role in EPO regulation during kidney disease progression. An increase in the expression of DNA methyl transferases and hypermethylation of Epo 5′-regulatory elements F I G U R E 7 Stimulation of EPO synthesis in fibrotic kidneys following pharmacologic HIF-PHD inhibition.…”
Section: Discussionmentioning
confidence: 99%
“…In this hypothetical model, renal "microenvironmental relative hyperoxia" is caused by decreased oxygen consumption of damaged tubules during the course of the disease, which leads to an attenuated hemoglobin oxygen desaturation of the capillary blood in the vicinity of the pericytic Epo-producing (REP) cells. Consequently, intracellular pO 2 levels in REP cells exceed the normal hypoxic set point required for Epo production, leading to renal anemia expression in ESRD [35]. Of note, TGFβ has recently been shown to suppress HIF-2α and Epo expression [96], which may thus represent a transdifferentiation-independent direct function of the TGFβ pathway.…”
Section: Why Do Rep Cells Fail To Produce Epo In Chronic Kidney Disease?mentioning
confidence: 99%